2015
DOI: 10.22146/gamaijb.25799
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Yemeni Customers’ Intention to Adopt Takaful Products

Abstract: The purpose of this study is to examine the Yemeni customers’ intention to adopt Takaful products, and to explore the potential factors that influence their decision. This study applies SEM and one sample t-test to analyse the collected data. The results indicate that among the factors included in this study, only compatibility positively and significantly affects the adoption intention. This is the first study that addresses the adoption of Takaful products in Yemen and the factors that influence it. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Siala (2013) further found impressive involvement of religious motive behind the consumption of religiously compliant services. Moreover, Echchabi and Ayedh (2015) and Husin and Rahman (2016) supported the argument that there is a significant impact of religious values toward the adoption of Takaful insurance.…”
Section: Takaful (Islamic Insurance) Productsmentioning
confidence: 59%
See 1 more Smart Citation
“…Siala (2013) further found impressive involvement of religious motive behind the consumption of religiously compliant services. Moreover, Echchabi and Ayedh (2015) and Husin and Rahman (2016) supported the argument that there is a significant impact of religious values toward the adoption of Takaful insurance.…”
Section: Takaful (Islamic Insurance) Productsmentioning
confidence: 59%
“…Similarly, Langer (2014) argued, an individual will hesitate toward innovation if it is not permissible under his/her religion. Thambiah et al (2010), Hussain and Pasha (2011), Echchabi and Ayedh (2015) noted, Takaful insurance works under Islamic Sharia laws. Therefore, individuals with more religious inclinations tend to adopt Takaful insurance because of congruence with their beliefs and social norms.…”
Section: Takaful (Islamic Insurance) Productsmentioning
confidence: 99%
“…As per the findings of Echchabi and Ayedh (2015), Echchabi and Echchabi (2013) and Reuters (2016), the Takaful insurance market is clustered in mostly "Gulf Cooperation Council" countries. Saudi Arabia is at the first place with the highest contribution volume, followed by Malaysia (Kaunain and Akhtar, 2016).…”
Section: Takaful Today and Tomorrowmentioning
confidence: 76%
“…The adoption of Takaful business is directly affected by three main factors such as subjective norm, attitude and perceived behavioral control (Abdulsater, 2014). Likewise, many studies have confirmed several factors such as religiosity, consumer knowledge, accessibility, situational factors and demographic variables, which have driven the adoption of Takaful insurance products (Hassan and Abbas, 2019;Echchabi and Ayedh, 2015;(Husin and Rahman, 2016;. The Takaful operators must devise more innovative products and arrange awareness programs through training and advertisement channels.…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation